PENERAPAN MODELLEARNING TOGETHER DALAM MENINGKATKAN KEMAMPUAN GURU MENYUSUN RPP DI SEKOLAH BINAAN KECAMATAN MEDAN AREA - Jonter Hutagalung (Universitas Negeri Medan, 2017)
Abstract :Implementation of Learning Together Model In Improving Teacher's Capacity of Preparing RPP in Binuran District of Medan Area.This study aims to improve the ability of teachers in preparing the Learning Implementation Plan through the implementation of cooperative method of Learning Together model in the Binaan school district Medan Area Medan city lesson 2015/2016. The study was conducted in SMP Negeri 13 Medan with Subject in research is the teacher of subjects of Christian Religious Education amounted to 9 people from the Binaan School of Medan Area Medan sub district. Based on the analysis in cycle I, from 10 aspects of observation there are 7 aspects get enough category and 3 aspects in the category less. Furthermore, in Cycle II shows 10 aspects of observation entirely get good category and even some aspects almost reach the category very well. The results of this study indicate that the method of learning together can improve the competence of teachers in preparing the RPP. It can be proven from the result of teacher competence assessment in preparing the RPP from Cycle I to Cycle II Keywords: Ability, Teacher, PAK, RPP, Learning Together Method Abstrak :Penerapan Model Learning Together Dalam Meningkatkan Kemampuan Guru Menyusun RPP Di Sekolah Binaan Kecamatan Medan Area. Penelitian ini bertujuan untuk meningkatkan kemampuan guru dalam menyusun Rencana Pelaksanaan Pembelajaran melalui penerapan metode kooperatif model Learning Together di Sekolah Binaan kecamatan Medan Area kota Medan tahun pelajaran 2015/2016. Penelitian dilakukan di SMP Negeri 13 Medan dengan Subjek dalam penelitian adalah guru pengampu mata pelajaran Pendidikan Agama Kristen berjumlah 9 orang dari Sekolah Binaan kecamatan Medan Area kota Medan. Berdasarkan analisa pada siklus I, dari 10 aspek pengamatan terdapat 7 aspek mendapatkan kategori cukup dan 3 aspek dalam kategori kurang. Selanjutnya, pada Siklus II menunjukkan 10 aspek pengamatan seluruhnya mendapatkan kategori baik bahkan beberapa aspek hampir mencapai kategori sangat baik. Hasil penelitian ini menunjukkan bahwa metode learning together dapat meningkatkan kompetensi guru dalam menyusun RPP. Hal itu dapat dibuktikan dari hasil penilaian kompetensi guru dalam menyusun RPP dari Siklus I ke Siklus II Kata Kunci :Kemampuan, Guru, PAK, RPP, Metode Learning Together